2019
DOI: 10.1021/acs.chemrev.8b00737
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Tetrapeptides from Nature and Design: A Review of Synthetic Methodologies, Structure, and Function

Abstract: Small cyclic peptides possess a wide range of biological properties and unique structures that make them attractive to scientists working in a range of areas from medicinal to materials chemistry. However, cyclic tetrapeptides (CTPs), which are important members of this family, are notoriously difficult to synthesize. Various synthetic methodologies have been developed that enable access to natural product CTPs and their rationally designed synthetic analogues having novel molecular structures. These methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 273 publications
0
37
0
Order By: Relevance
“…The linear precursors were synthesized using a solid-phase Fmoc-chemistry method on a 2-chlorotrityl resin, while the cyclic products were obtained through cyclization of the linear peptides in the solution phase. The cyclization site always involved a proline residue at the N-terminus, because the proline residue is a β-turn inducer that can facilitate cyclization [6,7,14]. The synthesis of all peptides began with the attachment of isoleucine to the 2-chlorotrityl resin, which resulted in an isoleucine-resin with loading values in the range of 0.61-0.90 mmol g −1 (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The linear precursors were synthesized using a solid-phase Fmoc-chemistry method on a 2-chlorotrityl resin, while the cyclic products were obtained through cyclization of the linear peptides in the solution phase. The cyclization site always involved a proline residue at the N-terminus, because the proline residue is a β-turn inducer that can facilitate cyclization [6,7,14]. The synthesis of all peptides began with the attachment of isoleucine to the 2-chlorotrityl resin, which resulted in an isoleucine-resin with loading values in the range of 0.61-0.90 mmol g −1 (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…During the coupling reactions in the presence of the HATU/HOAt reagent, it was found that triple coupling protocols were needed for the effective coupling between valine and isoleucine as well as between leucine and valine. The presence of the β-branched residue of valine could represent an issue in the synthesis [ 6 , 7 ]. The synthesis of all linear peptides resulted in percentage yields in the range of 29.9–60.8% ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As was mentioned above, peptide synthesis continues to be one of the areas of greatest interest in organic chemistry. This is due to the fact that peptides have many diverse applications, not only in the synthesis of organic compounds, but most importantly in the food and pharmaceutical industry [ 110 , 111 , 112 ]. In this regard, in recent years mechanochemistry has played an important role in the green synthesis of these compounds [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ].…”
Section: Mechanochemistrymentioning
confidence: 99%
“…This is especially the case when libraries of macrocyclic compounds obtained by cost-efficient parallel chemistry methods are considered. Many recent advances in this area were aimed at the synthesis of cyclic peptides or peptidomimetics, [12][13][14][15][16][17][18][19][20][21] other important success stories include the use of multicomponent reactions [21][22][23][24] and DNA-encoding technology. [25,26] Another synthetic methodology that is especially interesting for the construction of non-peptidic macrocycles is diversity-oriented synthesis (DOS).…”
Section: Introductionmentioning
confidence: 99%